Influence of Sous Vide Cooking on Ground Beef Patties - Savannah L. Douglas; Gabriela M. Bernardez-Morales; Brooks W. Nichols; Aeriel D. Belk; Tristan M. Reyes; Jase J. Ball; Jason T. Sawyer (Foods, 2023)
With rising consumer demand for fast-food options, quick-service restaurants are constantly developing new menu items to attract consumers. Sous vide cookery has become popular for the in-home and fine dining consumer but has not been considered the first cooking option for quick service applications. Therefore, ground beef patties were manufactured to measure the influence of sous vide cooking time on the patty characteristics of moisture, color, and objective tenderness. Patties were randomly assigned a sous vide cooking time of 30, 60, or 90 min and then grilled to an internal temperature of 71.1 °C. Patties sous vide cooked for 30 min exhibited the greatest (p < 0.05) cook loss, Allo–Kramer Shear Force (AKSF) and were darker (L*) than patties sous vide cooked for 60 or 90 min. Additionally, neither internal redness, calculated spectral values of chroma, hue angle, or red-to-brown differed (p > 0.05) regardless of sous vide cooking time. Sous vide cooking duration prior to grilling the ground beef patties altered the moisture, color, and objective texture characteristics of ground beef patties.